Complications of Nd: YAG Laser Capsulotomy - Bilal Bashir, Asif Iqbal, Adnan Alam, Bilal Khan, Mumtaz Alam, Mir Ali Shah (Pakistan Journal of Ophthalmology, 2014)
Purpose: To evaluate the complications of Nd: YAG laser capsulotomy. Material and Methods: It was a prospective study conducted from May 2012 to May 2013 at Khyber Eye Foundation Peshawar. 437 eyes of 406 patients were included in the study. Before performing YAG laser detailed history was taken and complete ocular examination was performed. A consultant ophthalmologist performed all YAG laser capsulotomies. Follow up was done at 1 day, 1, 2 and 4 weeks. Detail eye examination was performed at each visit to look for any complications. Results: Out of the 406 patients 189 (46.55%) were male and 217 (53.44%) were female. Mean age of the patients was 56.7 years. A variety of complications were noted after YAG laser capsulotomy. Intraocular lens pitting was the most common complication seen in 56 eyes (12.81%). Transient rise of intraocular pressure was seen in 38 eyes (8.69%) and cystoid macular edema was seen in 17 eyes (3.89%). Serious complications such as retinal detachment and endophthalmitis were seen in 2 eyes (0.45%) and 1 eye respectively (0.22%). Conclusion: A number of complications can occur after Nd: YAG laser capsulotomy. The most common of these complications are intraocular lens pitting, transient intraocular pressure elevation and cystoid macular edema. Key words: Intraocular lens, Capsulotomy, Cystoids macular edema.